The roots of rough justice: origins of American lynching - Pfeifer, Michael James (Univ. of Illinois Press, 2011)
Collective violence in the British Atlantic -- Vigilantes, criminal justice, and Antebellum cultural conflict -- Racial and class frontiers: lynching and social identity in Antebellum America -- Lynchers versus due process: the forging of rough justice -- The Civil War and reconstruction and the remaking of American lynching -- Epilogue